The task of determination of requirements at printing mixed ink - Турчинова, Галина Ивановна; Левыкин, Игорь Викторович; Никулина, Мария Юрьевна; Коваленко, Елена Константиновна (Eastern-European Journal of Enterprise Technologies, 2010)
At the print mixed ink the executor of the order has the problem of exact and uniform playback of color under the directory on a print, saving of color and obtaining of the colors which are distinct from colors of a triad costs colors.